2012
DOI: 10.1016/j.neuint.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Evoked dopamine overflow is augmented in the striatum of calcitriol treated rats

Abstract: Calcitriol, the active metabolite of vitamin D, has been shown to have significant effects on the brain. These actions include reducing the severity of some central nervous system lesions, possibly by upregulating trophic factors such as glial cell line-derived neurotrophic factor (GDNF). GDNF has substantial effects on the nigrostriatal dopamine (DA) system of young adult, aged and lesioned animals. Thus, the administration of calcitriol may lead to significant effects on nigrostriatal DA neuron functioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 44 publications
1
33
0
1
Order By: Relevance
“…Progression of PD symptoms is associated with the degeneration of dopaminergic neurons. As previously outlined, preclinical studies in neurotoxicity animal models of this disease confirm that 1,25(OH) 2 D 3 can restore dopamine levels in striatum and ameliorate dopamine neuron death induced by intra-cerebral administration of 6-OHDA (Wang et al, 2001;Smith et al, 2006;Sanchez et al, 2009;Cass et al, 2012Cass et al, , 2014. Cass et al and Sanchez et al have showed that vitamin D increases GDNF in the lesioned striatum indicating this trophic agent may be the mediating factor for vitamin D's neuroprotective actions on dopamine neurons.…”
Section: 25(oh) 2 D 3 Directly Modulates Th Expression In Neuronal mentioning
confidence: 71%
See 2 more Smart Citations
“…Progression of PD symptoms is associated with the degeneration of dopaminergic neurons. As previously outlined, preclinical studies in neurotoxicity animal models of this disease confirm that 1,25(OH) 2 D 3 can restore dopamine levels in striatum and ameliorate dopamine neuron death induced by intra-cerebral administration of 6-OHDA (Wang et al, 2001;Smith et al, 2006;Sanchez et al, 2009;Cass et al, 2012Cass et al, , 2014. Cass et al and Sanchez et al have showed that vitamin D increases GDNF in the lesioned striatum indicating this trophic agent may be the mediating factor for vitamin D's neuroprotective actions on dopamine neurons.…”
Section: 25(oh) 2 D 3 Directly Modulates Th Expression In Neuronal mentioning
confidence: 71%
“…A number of studies have shown that 1,25(OH) 2 D 3 can act as a neuroprotective agent for dopaminergic neurons (Wang et al, 2001;Cass et al, 2006;Smith et al, 2006;Sanchez et al, 2009;Cass et al, 2012Cass et al, , 2014. These data and the epidemiological findings linking low levels of vitamin D with increased risk of Parkinson's disease (PD) (Newmark and Newmark, 2007;Evatt et al, 2008Evatt et al, , 2011Knekt et al, 2010;Peterson et al, 2013) have led to a clinical trials of vitamin D in this disease.…”
Section: 25(oh) 2 D 3 Directly Modulates Th Expression In Neuronal mentioning
confidence: 99%
See 1 more Smart Citation
“…Calcitriol has been shown to increase expression or release of GDNF in various cell lines [1416] and in vivo administration has been shown to increase expression and protein levels of GDNF in the brain [1720]. GDNF has potent effects on brain DA systems, and because of this it has been examined in several animal models of PD where it was shown to have neuroprotective or restorative effects [2125].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, vitamin D has been shown to protect against methamphetamine-induced reductions in dopamine and serotonin in both the striatum and accumbens (Cass et al, 2006). Vitamin D treatment has also been shown to increase both potassium-and amphetamine-evoked overflow of striatal dopamine as well as increase substantia nigra tissue levels of dopamine and its main metabolites (Cass et al, 2012).…”
Section: Neurotransmissionmentioning
confidence: 99%